2019
DOI: 10.21161/mjm.180155
|View full text |Cite
|
Sign up to set email alerts
|

Local strains Aspergillus oryzae KKB4 and Rhizopus oryzae KP1R1 as a reducing and detoxifying agents for deoxynivalenol

Abstract: Aims: Deoxynivalenol is a type B trichothecene produced by Fusarium graminearum that can cause serious health problems in human and livestock. The present study aimed to reduce and detoxify deoxynivalenol using a local strain Aspergillus oryzae KKB4 and Rhizopus oryzae KP1R1. Methodology and results: Corn as solid substrate artificially inoculated with F. graminearum bio 163252 to produce deoxynivalenol. Deoxynivalenol contaminated corn then inoculated with A. oryzae KKB4 and R. oryzae KP1R1. During fermentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Aspergillus oryzae KKB4 and Rhizopus oryzae KP1R1 were inoculated into DON-contaminated corn and fermented for 10 days, which resulted in DON reduction by 65.91% and 56.82%, respectively. Toxicity analysis showed that the degradation products did not affect the growth of Saccharomyces cerevisiae ( Arifin et al, 2019 ). Moreover, the DON degradation percentage in corn medium was as high as 92% after culture of Aspergillus oryzae (5509NRRL) for 21 days ( Tran and Smith, 2014 ).…”
Section: Biological Methodsmentioning
confidence: 99%
“…Aspergillus oryzae KKB4 and Rhizopus oryzae KP1R1 were inoculated into DON-contaminated corn and fermented for 10 days, which resulted in DON reduction by 65.91% and 56.82%, respectively. Toxicity analysis showed that the degradation products did not affect the growth of Saccharomyces cerevisiae ( Arifin et al, 2019 ). Moreover, the DON degradation percentage in corn medium was as high as 92% after culture of Aspergillus oryzae (5509NRRL) for 21 days ( Tran and Smith, 2014 ).…”
Section: Biological Methodsmentioning
confidence: 99%
“…Arifin et al. (2019) showed that local strains A. oryzae KKB4 and R. oryzae KP1R1 (0.1% rough powder) could detoxify DON (500 ng/mL) in corn, and the reduction rate of DON was 65.91% and 56.82%, respectively, after 10 days of fermentation.…”
Section: Don Biological Detoxification Methods and Nutritional Mitiga...mentioning
confidence: 99%
“…Tian, Tan, Liu, Yan, et al (2016) indicated that Trichoderma strains possess a selfprotection mechanism as plants to detoxify DON (57 μg/g) into D3G when competing with F. graminearum. Arifin et al (2019) showed that local strains A. oryzae KKB4 and R. oryzae KP1R1 (0.1% rough powder) could detoxify DON (500 ng/mL) in corn, and the reduction rate of DON was 65.91% and 56.82%, respectively, after 10 days of fermentation.…”
Section: Aspergillusmentioning
confidence: 99%